Parity of participation for autistic students: Mapping provision across UK higher education institutions. Issue 1 (May 2022) - Vincent, Jonathan; Rowe, Helen; Johnson, Jo
This paper systematically identifies, maps and evaluates specific types of provision for autistic students published on university websites at 120 institutions throughout the UK. Within these data we identify trends in relation to geographical region, university group, and the Teaching Excellence Framework rating. We employ Nancy Fraser's theory of social justice to unpack the reasons that underlie the differentials in provision across UK higher education institutions. Findings identify eight categories of provision tailored specifically for autistic students from 'supporting transition to university' to 'social groups' and suggest that there are institutions across the UK with evidence of more developed provision. Our data show, however, that resources and provision are not distributed equitably, raising implications for autistic students' parity of participation in higher education.